Intrinsic ferroelectric CuVP2S6 for potential applications in neuromorphic recognition and translation - Chunyu Zhao; Weikang Dong; Yang Yang; Hongbin Yu; Jingyi Duan; Denan Kong; Kangshu Li; Xiaocang Han; Chao Yun; Tingjun Wang; Ping Wang; Yang Zhao; et al. (Nature Communications)
Abstract Two-dimensional ferroelectric materials hold promises for non-volatile memory and integrated electronic circuits. However, direct synthesizing and understanding the ferroelectric mechanism of two-dimensional room-temperature ferroelectrics remains challenging. Here, we report the synthesis of intrinsic room-temperature ferroelectric CuVP2S6 via spatially confined chemical vapor deposition method, as demonstrated by second harmonic generation and piezoresponse force microscopy measurements. Importantly, we experimentally uncover the ferroelectric mechanism of CuVP2S6, which originates from the movement of Cu ions, as confirmed by scanning transmission electron microscopy. Additionally, we construct an optoelectronic CuVP2S6 synaptic device, which enables a smooth transition from optical character recognition to neural machine translation using a transformer architecture. Our study not only elucidates the ferroelectric mechanism of two-dimensional metal phosphorus sulfide compounds but also integrates optical character recognition and neural machine translation within a single material, offering significant opportunities for neuromorphic computing systems.